GEOGRAPHIC ACCESS DISPARITIES TO CLINICAL TRIALS IN RETINOPATHY OF PREMATURITY IN THE UNITED STATES. Issue 11 (November 2021) - Soares, Rebecca R.; Cai, Louis Z.; Bowe, Theodore; Samuelson, Annika G.; Liu, Catherine K.; Parikh, Devayu; Patel, Samir N.; Hinkle, John W.; Yonekawa, Yoshihiro
Abstract : Background/Purpose: To identify geographic and socioeconomic variables predictive of residential proximity to retinopathy of prematurity (ROP) clinical trial locations. Methods: This cross-sectional epidemiological study used census tract–level data from three national public data sets and trial-level data from ClinicalTrials.gov . Socioeconomic predictors of driving distance and time to the nearest ROP clinical trial location were identified. Primary outcomes were time >60 minutes and distance >60 miles traveled to the nearest ROP clinical trial site. Results: Multivariate analysis showed that residents were more likely to travel >60 minutes to the nearest ROP clinical trial site if they lived in census tracts that were rural (adjusted odds ratio 1.20, P = 0.0002), had higher percentages of the population living ⩽ federal poverty level (fourth quartile vs. first quartile, adjusted odds ratio 1.19, P < 0.0001), or had less education (associate vs. bachelor's degree, adjusted odds ratio 1.01, P <0.007). By contrast, counties with higher percentages of births with birth weight <1500 g (adjusted odds ratio 0.88, P = 0.0062) were less likely to travel >60 minutes. Similar variables predicted travel distance. Conclusion: Although counties with higher incidences of very low-birth-weight infants were closer to ROP clinical trial sites, residents living in rural and low-income census tracts had significantly greater travel burdens. Abstract : There are strong geographic trends in access to clinical trial sites for retinopathy of prematurity. Those with higher travel burden are more likely to reside in rural, low-income areas. Conversely, patients from counties with higher rates of very low-birth-weight infants are less likely to have increased travel burdens.